Answer:
1. (b)
2. (b)
Explanation:
1.
We have,
![x-(1)/(x)=5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ii94tv1xrvidig1fpbwu41cqve84prb1ol.png)
Now, squaring both sides, we get
.......(1)
Now, using the identity
in the LHS of the equation (1), we get
⇒
![x^2+(1)/(x^2)-2=25](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mfpc3i7le5xymdfqkv5h1emyj4r7esiu4k.png)
⇒
![x^(2) +(1)/(x^2)=25+2=27](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p5p7djjm3d23mx5rmk4ui9o5g5eb4ey4x8.png)
∴ The correct answer is option (b).
2.
We have,
![x-(1)/(x)=5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ii94tv1xrvidig1fpbwu41cqve84prb1ol.png)
Now, squaring both sides, we get
.......(1)
Now, using the identity
in the LHS of the equation (1), we get
⇒
![x^2+(1)/(x^2)-2=25](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mfpc3i7le5xymdfqkv5h1emyj4r7esiu4k.png)
⇒
.......(2)
Again, squaring both sides of equation (2), we get
.......(3)
Now, using the identity
in the LHS of the
equation (3), we get
![(x^2)^2+((1)/(x^2))^2+2* x^2* (1)/(x^2)=729](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a9baged4hdbx2sii08w92zik91t09huwr2.png)
⇒
![x^4+(1)/(x^4)+2=729](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hrgxfkrukzf22b4huvcy5eu4b6e9s4gerl.png)
⇒
![x^4+(1)/(x^4)=729-2=727](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xbdin6j8ltxc2upk5thtwfea6i6gayldnl.png)
∴ The correct answer is option (b).